Closing the Divide: communicating with millennials in the workplace - Kavan, Danielle (Kansas State University, 2011)
Although some literature exists to describe the difference between Millennials and other generations in the workplace, I have developed my own ten steps that will help match what Millennials want from their bosses and workplace with what the company needs from them based on the research available and my own personal experience in a a workplace that did not cater to Millennials.
Keywords: Millennials; Communication; Symbolic Interactionism; Workforce; Communication (0459)